Innovative inorganic-organic nanohybrid materials: Coupling quantum dots to carbon nanotubes - Schulz-Drost, Christian; Sgobba, Vito; Gerhards, Christina; Leubner, Susanne; Krick Calderon, Rafael; Ruland Palaia, Andres; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2010)
Inorganic meets organic: Covalent bonds (peptide condensation) and noncovalent interactions (π-π stacking) have been employed en route toward versatile donor-acceptor inorganic- organic nanohybrids, QD-pyrene/SWNT. A charge-transfer event within the hybrid transforms the excitonic state of the quantum dot into a charge-transfer state that has a lifetime of several nanoseconds. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.